Case Report: Prolonged CSF PCR Positivity in a Neonate With GBS Meningitis - Alruqaie, Nourah; Falatah, Yara; Alzahrani, Fawaz; Alharbi, Musaed (Frontiers in Pediatrics, 2021)
Bacterial meningitis is one of the critical diseases that needs to be diagnosed and treated promptly. Recent diagnostics of high sensitivity and specificity rates such as PCR helped with such presentation, especially in cases with prior antibiotics that led to culture negativity. However, the time window of PCR positivity is not well studied, with scattered reports of different periods of positivity. Here we report a case of neonatal GBS meningitis with positive PCR for more than 80 days from starting antibiotics.